Web-based commercialization system to improve efficiency and logistics management at LAKTOMART S.A. - Villanueva Ramos, Juan Rodrigo (2025)
The purpose of the research was the improvement of efficiency and logistics management in the area of ​​commerce and distribution of the LAKTOMART S.A. company through the development of an online platform using the Model-View-Controller (MVC) architecture. A pre-experimental design was adopted with a quantitative orientation and had an explanatory scope. The methodology applied was the RUP (Rational Unified Process). For the implementation of the web application, HTML5, CSS3, JQuery V3.7.1, PHP V8.2.0 were used with the Laravel V10 framework. .48.180, domPDF V0.8 and MySQL V8.0.31 for database administration in addition, the evaluation of the economic indicators linked to the sales and distribution subsystems generated positive results that confirmed the economic viability of the developed system in question. The hypotheses were evaluated using the Shapiro-Wilk normality tests, and inferential statistical tests were applied, such as the student’s t test for related samples and the non-parametric Mann-Whitney test for independent samples, managing a significance level of. 5%. R statistical software was used for all tests. Based on the findings, it was concluded that the online platform with MVC architecture improves efficiency and effectiveness in LAKTOMART S.A.'s electronic business.